2017
DOI: 10.1111/1556-4029.13556
|View full text |Cite
|
Sign up to set email alerts
|

“Undoing” (or Symbolic Reversal) at Homicide Crime Scenes

Abstract: A closed case file review of a nonrandom national sample of 975 homicides disclosed 11 cases (1.13%) of undoing, wherein offenders engaged in crime scene behavior that has been considered an attempt to symbolically reverse the murder. The frequency of the various methods of undoing involved the use of blankets to cover the victim's body (55%), positioning the body (55%), use of a bed or couch (42%), washing the body (36%), using pillows (36%), as well as removing clothing and adding other types of adornments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…In the future, the associations of the gender of the victim, use of ligature, and body transportation need to be examined. Our findings show that in homicide investigations a thorough examination of the victims' injury locations and evidence of homicidal behaviors at the crime scene is essential (5,6). Further studies are needed, especially of offenders' behaviors, particularly those directed at the bodies of their victims, such as covering and hiding them.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the future, the associations of the gender of the victim, use of ligature, and body transportation need to be examined. Our findings show that in homicide investigations a thorough examination of the victims' injury locations and evidence of homicidal behaviors at the crime scene is essential (5,6). Further studies are needed, especially of offenders' behaviors, particularly those directed at the bodies of their victims, such as covering and hiding them.…”
Section: Discussionmentioning
confidence: 89%
“…Homicide research on body transportation is scarce. Previous studies have emphasized that it is crucial to conduct a thorough analysis of the behaviors evidenced in a homicide, especially those related to the body of the victim . Prior studies on homicide have examined only a small proportion of the homicide cases in which the body of the victim was transported from the location of the homicide .…”
mentioning
confidence: 99%
“…While there is an extensive body of research on child maltreatment in South Korea, studies focusing on offense behaviors have been limited. Offense behaviors include the various actions and methods of perpetrators carried out at a crime scene . For instance, previous research on child abuse reported the use of blunt force by perpetrators during offenses, and perpetrators sometimes inflict head injuries and bite marks during the course of child abuse .…”
mentioning
confidence: 99%
“…KEYWORDS: forensic science, virtual crime scene, 3D motion capture, dynamics reconstruction, 3D model buildings, forensic injury biomechanics Crime scene investigation is fundamental in forensic cases (1). During the inspection of the crime scene, the forensic scientists collect scientific evidence in order to analyze the phases of a crime, preserve trace evidence, and search for the identity of the killer.…”
mentioning
confidence: 99%
“…Crime scene investigation is fundamental in forensic cases . During the inspection of the crime scene, the forensic scientists collect scientific evidence in order to analyze the phases of a crime, preserve trace evidence, and search for the identity of the killer.…”
mentioning
confidence: 99%